The Effectiveness of Flash Cards in Improving Reading Skills of Elementary School Students - Annisyah; Eny Munisah (Journal for Lesson and Learning Studies, 2025)
The challenge of improving elementary school students' reading skills remains a pressing issue in education. This study aims to evaluate the impact of flash cards on enhancing various dimensions of reading skills, including letter recognition, vocabulary mastery, phonetic ability, and reading comprehension. Using a systematic literature review approach, the research synthesizes findings from eight scientific articles published between 2019 and 2023. The articles were selected based on strict eligibility criteria, including relevance, a citation count exceeding 10, and accessibility. Data were sourced from the Google Scholar database using keywords such as "flash card," "reading," and "elementary school." The results indicate that flash cards significantly enhance students' reading abilities, fostering improvements in fluency, intonation, motivation, and comprehension. Additionally, this tool proves effective for students with learning disabilities and shows promise when integrated with other instructional strategies, such as the probing prompting model. In The study concludes that flash cards are a practical, flexible, and effective medium for improving reading skills in both regular and special-needs students. The findings underscore the importance of integrating innovative visual learning tools in classrooms to optimize literacy outcomes.